Test Data Generation based on Artificial Intelligence Impacts Banking IT - Joerg STRAESSER; Zuzana STOLICNA (Communications of International Proceedings, 2020)
The scope of this publishing item is to reflect the research status around test data generation by Artificial Intelligence methods and what could be the influence factors for the decision of  the IT management in banking sector for the professional usage of AI. This article also aims to outline the differences between test data generation by traditional approach versus Machine /Deep Learning algorithms as subset of AI.
Keywords: Artificial Intelligence; Banking; IT Management; Product brand; Testing; Test data.